Answer:
f(4) = 22
Step-by-step explanation:
I think that you type wrongly.
we have f(1) = -5
and f(n) = f(n-1) + 9
Find f(4)
Then
with n= 2 we have f(2) = f(1) + 9 = - 5+ 9= 4
with n= 3 we have f(3) = f(2) + 9 = 4 + 9= 13
and finally with n= 4 we find f(4) = f(3) + 9 = 13+ 9= 22
So f(4) = 22
Hope you understand.
Answer: I believe the answer would be about 1
hope this helps
D.36 60 .... because 6 times 6 is 36 and 6 times 10 is 60
Answer:
A) 3 in
General Formulas and Concepts:
<u>Pre-Algebra</u>
Order of Operations: BPEMDAS
- Brackets
- Parenthesis
- Exponents
- Multiplication
- Division
- Addition
- Subtraction
Equality Properties
<u>Geometry</u>
- Surface Area of a Sphere: SA = 4πr²
- Diameter: d = 2r
Step-by-step explanation:
<u>Step 1: Define</u>
SA = 23 in²
<u>Step 2: Find </u><em><u>r</u></em>
- Substitute [SAS]: 23 in² = 4πr²
- Isolate <em>r </em>term: 23 in²/(4π) = r²
- Isolate <em>r</em>: √[23 in²/(4π)] = r
- Rewrite: r = √[23 in²/(4π)]
- Evaluate: r = 1.35288 in
<u>Step 3: Find </u><em><u>d</u></em>
- Substitute [D]: d = 2(1.35288 in)
- Multiply: d = 2.70576 in
- Round: d ≈ 3 in